Efforts to Improve Students' Cognitive Learning Outcomes by Using Demonstration Methods in Fiqh Subjects on Hajj Subjects (Classroom Action Research on Class V Students of MI Al Istiqomah Katapang Bandung District) - Faturahman, Rizqi; Hadi, Muhammad Sofian; Surizkika, Aldi (International Journal of Integrative Sciences, 2025)
This study seeks to enhance students' cognitive learning outcomes in Fiqh subjects focused on Hajj through the implementation of the demonstration method. In Indonesia, the education system continues to grapple with challenges, particularly regarding teaching methods that often lack variety. This research emphasizes the effectiveness of the demonstration method in Fiqh education, especially in relation to Hajj, with the goal of fostering a deeper understanding among students. The findings indicate that this method not only boosts student engagement but also reinforces conceptual comprehension and improves overall learning outcomes. Adopting a holistic approach, the study aims to cultivate insightful, empathetic, and socially responsible individuals capable of making meaningful contributions to society. Results indicate a progressive increase in student understanding of Hajj Fiqh throughout the cycles of learning facilitated by the demonstration method